CLINICAL AND FUNCTIONAL ASSESSMENT OF THE EFFICIENCY OF LASER CORRECTION OF GENITAL PROLAPSE DISORDERS IN WOMEN - Dilchekhra Yu. Yuldasheva; Masuda G. Giyasova; Feruza D. Karimova (Central Asian Journal of Medicine, 2022)
The purpose. Evaluation of the effectiveness of the method of laser correction of pelvic floor incompetence and its impact on the clinical and functional state and quality of life (QOL) of women with genital prolapse. Material and research methods. Investigated 102 patients with violations of the architectonics of the pelvic organs, whose age was 57 ± 13.6 years. The studied patients, depending on the method of genital prolapse correction, were divided into 2 groups: the 1st main group (n = 52) with the use of laser therapy and the 2nd comparison group (n = 50) with surgical treatment. The POP-Q system was used to assess the degree of genital prolapse. The severity of manifestations of genital prolapse before and after treatment was assessed using the PFDI-20 questionnaire. As a way to assess the QoL of women with PG, a questionnaire was conducted using the EuroQol - 5D and EQ-VAS questionnaires before and after treatment. Results. In the course of the study, it was revealed that the quality of life and clinical manifestations of genital prolapse in women after correction of genital incompetence by non-invasive and invasive methods had significant differences in the compared groups depending on the degree of prolapse. Conclusion. Thus, fractional laser therapy turned out to be more effective than surgical correction for grade 1–2 genital prolapse as a high-tech minimally invasive method, the advantage of which was to improve the quality of life and clinical and functional state of women with pelvic organ prolapse.